False Alarms in the Decision Support System of the State Fire Service - Marek Marzec; Jacek Kuskowski (Safety & Fire Technology, 2022)
Aim: The aim of the article is to analyse the recording of false alarm cases using the Decision Support System of the State Fire Service (SWD PSP) in terms of certain requirements for a firefighter creating information from an incident. The cases under consideration belong to one of the types of incidents involving fire protection units. Introduction: Since 1993, when PSP began recording incidents using a database system, the scope of information on false alarms has not changed. To this day, in the incident sheet constituting Annex No. 5 to the regulation on the detailed organization of the national rescue and firefighting system, there is no false alarm as a separate type of incident apart from fire and local emergency. A detailed analysis of the data on false alarms was created in connection with the need to prepare a speech by representatives of KG PSP during a scientific conference organized by CNBOP-PIB entitled “False alarms generated by fire alarm systems”. The authors did not limit themselves to the analysis of alarms from detection installations, and the material was expanded to include a spatial analysis of the occurrence of such events. Methodology: The results of the authors’ own analyses performed on the basis of data collected in SWD PSP and software from the geographic information systems (GIS) were used. In their deliberations, the authors also relied on years of experience in creating and revising the rules for recording incidents in SWD PSP and building a new information system for fire protection units. Results: Zakres danych gromadzonych przez PSP w zakresie alarmów fałszywych jest niewystarczający do przeprowadzenia dokładnych i wnikliwych analiz, w szczególności w zakresie przyczyn wystąpienia, szczegółowych informacji o obiekcie (miejscu zdarzenia) oraz wyposażeniu budynków w systemy sygnalizacji pożarowej oraz inne ułatwiające lub utrudniające prowadzenie działań jednostkom ochrony przeciwpożarowej. Istnieje pilna potrzeba rozbudowania minimalnego zakresu danych niezbędnych do ewidencjonowania w bazach danych PSP. Przedstawione wyniki analiz wskazują również na niedostateczne rozgraniczenie pomiędzy miejscowym zagrożeniem a alarmem fałszywym. Najbliższa nowelizacja zasad ewidencjonowania zdarzeń ma zawierać zapisy, które powinny poprawić jakość danych. Dokładniejsza analiza będzie jednak możliwa dopiero po wdrożeniu nowobudowanego SWD PSP, uwzględniającego między innymi moduł operacyjnego katalogu obiektów. Conclusions: The scope of data collected by PSP on false alarms is insufficient to carry out accurate and thorough analyses, particularly with regard to the causes of occurrence, detailed information about the facility (site of the incident) and the equipment of buildings with fire alarm systems and others that facilitate or hinder the activities of fire protection units. There is an urgent need to expand the minimum scope of data needed to be recorded in PSP databases. The presented analytical results also indicate that there is insufficient distinction between a local emergency and a false alarm. The upcoming revision of the rules for recording events is expected to include provisions that should improve the quality of data. However, a more detailed analysis will be possible only after the implementation of the newly built SWD PSP, including, among other things, an operational module of the object catalogue. Keywords: false alarm, Decision Support System of the State Fire Service, principles of recording incidents, State Fire Service, spatial analysis